Far-infrared self-continuum absorption of H216O and H218O (15–500 cm−1). (April 2019) - Odintsova, T.A.; Tretyakov, M. Yu.; Zibarova, A.O.; Pirali, O.; Roy, P.; Campargue, A.
Highlights: Continuum absorption of H2 18 O and natural water is studied in the 15–500 cm −1 range. Self-continuum cross-section, CS, are derived in the 15–35 and 40–500 cm − 1 intervals. Water dimer is confirmed to bring the dominant contribution below 25 cm − 1 . The MT-CKD model overestimates by 30–100% the measured continuum. Irregular fluctuations of CS are related to the line shape of the resonant lines. Abstract: The water vapor continuum absorption is studied in a spectral range covering most of the pure rotational spectrum of water molecule up to 500 cm −1 . The continuum absorption was derived from the broadband water vapor spectra recorded by Fourier transform spectrometer equipped with the 151-m multipass gas cell at the AILES beam line of the SOLEIL synchrotron. The coherent (10–35 cm −1 ) and standard (40–500 cm −1 ) radiation modes of the synchrotron were used. In order to refine the magnitude and clarify the physical origin of the continuum, spectra of the two major water isotopologues, H2 16 O and H2 18 O, were considered. Recordings at several water vapor pressures were used to check the expected quadratic pressure dependence of the continuum. The new data extend and supplement previous measurements filling, in particular, the gap between 200 and 350 cm −1, which was never studied before. The H2 16 O and H2 18 O absorption continua in the range of 50–650 cm −1 show similar frequency dependence and magnitude. In particular, both continua exhibit a clear water dimer spectral signature near 15 cm −1, in good agreement with previous ab initio calculations. The present data confirm that the MT-CKD empirical continuum model widely used in atmospheric applications, overestimates importantly the continuum magnitude in the whole range of the rotational band. The observed irregular frequency dependence of the retrieved self-continuum cross-section values is tentatively interpreted as due to uncertainties on the resonance lines of the water monomer spectrum which is subtracted from the recorded spectra. On the basis of spectra simulations, the inadequate description of the line shapes in the range of the intermediate wings (detuning of 5–10 cm −1 from line center) and the uncertainties on the self-broadening coefficients of water monomer lines are identified as possible mechanisms responsible of the observed irregular fluctuations.